ANALISIS PENINGKATAN KONSISTENSI ILMIAH SISWA PADA PEMBELAJARAN DENGAN MENGGUNAKAN PENDEKATAN SCIENTIFIC BERBASIS MULTIREPRESENTASI - Iyon Suyana; Shelly Feranie (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
The research aimed to determine the improvement and description of students’ scientific consistency in a senior high school after learning using scientific approach based on multiple sepresentasi. The sampel of the research was 31 students with purposive sampling method. The research method used was quasi-experiment with one shot case study design experiment. To determine the studens’ scientific consistency, three-tier test with verbal question, image and mathematical question were applied. The result showed that there is an improvement of students’ scientific consistency in medium category, and for some particular subconcepts showed the improvement in low, medium and high categories. Keywords: scientific consistency, multirepresentation scientific approach